Sharia Governance Method And Balanced Scorecard In The Management of Sustainable Islamic Cooperative Businesses - Etom Katamsi; Euis Amalia; Arief Mufraini; Asyari Hasan (Amwaluna: Jurnal Ekonomi dan Keuangan Syariah, 2026)
Sharia governance is the most important thing in optimal performance measurement. Performance measurement is a necessity to be in accordance with the vision, mission, goals and strategies. One form of business institution that is expected to be appreciated by the middle to lower economic community is a non-bank financial institution in the form of a Sharia Savings and Loan and Financing Cooperative (KSPPS) which puts forward the concept of thinking and implementation of sharia economics, justice and help. The purpose of this research is to analyse the integration of Sharia Governance and Balanced Scorecard models in a sharia-based business so that the resulting performance becomes sustainable. The research methodology used is Mixed Methode the Explanatory Sequential Design with SEM-PLS analysis. This research can prove that Integrated performance has a strong influence on Sharia Governance and Balanced Scorecard, which has a very significant effect on Sustainable Business. The novelty of this research is the integration of Sharia Governance and Balanced Scorecard models for the performance of sustainable Islamic Cooperatives.  Sustainable aspects have a very significant effect on the performance of Islamic Cooperatives in the form of increased profits, concern for social programmes, and environmental responsibility, this is in accordance with the concept of maslahah in achieving benefits. The contribution of this research for academics is a reference to the literature on Islamic Cooperatives, for regulators or governments as policy input, while for practitioners as a reference for improving organisational performance and a deeper understanding of the management of KSPPS.